Tourism Development for Baysun SPA in Uzbekistan as a New Destination - Khusniddin, Egamnazarov; Mahammadsidik, Amonboev (European Journal of Life Safety and Stability (2660-9630), 2022)
Nowadays, Uzbekistan has concentrated on establishing small tourist zonesin mountainous regions in order to increase the number of local and international tourists visiting the places. Based on the government reforms, we have studied to develop aSPA tourist place in Baysun, Surxondaryo region, Uzbekistan. In this research, we approached to develop a new touristic place as a SPA tourism by Plog`s theory. The findings from this research can help both of the government and the stakeholders to organize a system forSPA tourism development in Baysun, Uzbekiston.